CADASTRE OF GROUNDS FOR BUILDING NEW POWER UNITS OF NUCLEAS POWER PLANTS USING MODERN GIS-TECHNOLOGIES - ASTASHKINA, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Going is examined near systematization of maximum factors of creation Cadastre of grounds for building new power units of Nucleas Power Plants using modern GIS-technologies.